2009
DOI: 10.1158/1078-0432.ccr-08-2262
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Immunosuppresive B7-H3 Ligand by Hormone-Treated Prostate Cancer Tumors and Metastases

Abstract: Purpose: Prostate cancer cells uniformly express the immune cell inhibitory B7-H3 ligand.Enhanced B7-H3 expression correlates with increased disease progression and cancer-specific death after radical prostatectomy (RP). Experimental Design: To further assess whether B7-H3 expression is hormone regulated and persists as a viable target during (or after) androgen-ablative therapy, we examined B7-H3 ligand expression within primary and metastatic cancer lesions in response to neoadjuvant hormone therapy (NHT) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 38 publications
3
50
0
2
Order By: Relevance
“…In other tumor entities, the frequency of tumor B7-H3-positive cases varied from 46% in RCC (22) to 96% in prostate cancer (46). As described by others (42,47), a low expression of both B7-H3 and B7-H4 with a score of 1 to 2 was detected in normal skin surrounding the benign lesions of the same patients ( Fig.…”
Section: Discussionsupporting
confidence: 58%
“…In other tumor entities, the frequency of tumor B7-H3-positive cases varied from 46% in RCC (22) to 96% in prostate cancer (46). As described by others (42,47), a low expression of both B7-H3 and B7-H4 with a score of 1 to 2 was detected in normal skin surrounding the benign lesions of the same patients ( Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Several studies have suggested that B7-H3 is also present in certain types of human cancer and plays critical roles in carcinogenesis and tumor progression [6]. Up-regulation of B7-H3 occurs in a wide range of cancers, such as prostate cancer, lung cancer, colorectal carcinoma, pancreatic cancer, ovarian carcinoma and gastric cancer [7][8][9][10][11][12]. These observations demonstrate that overexpression of B7-H3 may indicate an aggressive biologic role in carcinogenesis.…”
Section: Introductionmentioning
confidence: 83%
“…In this article, we have described identification and characterization of a panel of mAbs with specificity for B7-H3, a protein overexpressed on many cancers, including prostate (15)(16)(17), renal (18), pancreatic (19,20), colorectal (21), non-small cell lung (NSCLC; ref. 22), ovarian (23), bladder (24), melanoma (25), and neuroectodermal (25) cancers and postulated to mediate immunomodulatory activity (26).…”
Section: Discussionmentioning
confidence: 99%
“…Reports suggesting a costimulatory role in immune modulation for B7-H3 (27) have been countered by a preponderance of evidence suggesting a tumor-supportive role in terms of immunologic escape (11,(32)(33)(34) and increased resistance to treatment (35). Overexpression of B7-H3 has been correlated with disease severity and poor outcome in a growing number of cancer types, including pathologic indicators of aggressiveness and negative clinical outcome in prostate cancer (15)(16)(17), increased grade and decreased T-lymphocyte infiltration in tumor nests and stroma in colorectal cancer (21), and a reduction in T-lymphocyte infiltrates in NSCLC (22). B7-H3 expression on tumor-associated vascular endothelia suggests additional roles for B7-H3 that favor tumor growth and progression, albeit by mechanism(s) not yet uncovered.…”
Section: Discussionmentioning
confidence: 99%